Bone Mineral Density and Body Mass Index: The Practicable Interaction Between Bone Fragility and Obesity Interaction (Journal of Pharmaceutical Negative Results, 2022)
Background: Previous findings have shown that the body mass index (BMI) is related positively to bone mineral density (BMD). In patients with low BMI (<18.5 kg/m2), the levels of BMD have usually been decreased and the T-values have been low. The goal of the study is to assess weight-BMI-BMD relationships among743 healthy people from the Karachi Gulshan district.Methodology: The research comprised a population of 743 people classified into four BMI classes. The BMD measurement in all the study participants was done by using a Sonost 3000 (Ultrasound Bone Densiometer) from Osteosys CO. Ltd. Korea.Results: The findings of BMI and BMD correlation indicated that osteopenia was occur more in underweight individuals than the overweight and obese, while osteoporosis occurred more in those who were obese in the comparison under & overweight individuals.Conclusion: The study of the associations between BMI and BMD in both male and female participants revealed a strong positive association showed by Pearson's correlation analysis.